Fatigue limit of polycrystalline zirconium oxide ceramics: Effect of grinding and low-temperature aging. (August 2016) - Pereira, G.K.R.; Silvestri, T.; Amaral, M.; Rippe, M.P.; Kleverlaan, C.J.; Valandro, L.F.
Abstract: The following study aimed to evaluate the effect of grinding and low-temperature aging on the fatigue limit of Y-TZP ceramics for frameworks and monolithic restorations. Disc specimens from each ceramic material, Lava Frame (3M ESPE) and Zirlux FC (Ivoclar Vivadent) were manufactured according toISO:6872-2008 and assigned in accordance with two factors: (1) "surface treatment"-without treatment (as-sintered, Ctrl), grinding with coarse diamond bur (181 µm; Grinding); and (2) "low-temperature aging (LTD)" – presence and absence. Grinding was performed using a contra-angle handpiece under constant water-cooling. LTD was simulated in an autoclave at 134 °C under 2-bar pressure for 20 h. Mean flexural fatigue limits (20, 000 cycles) were determined under sinusoidal loading using stair case approach. For Lava ceramic, it was observed a statistical increase after grinding procedure and different behavior after LTD stimuli (Ctrl<Grinding; Ctrl<Ctrl Ltd; Grinding=Grinding Ltd); while for Zirlux, grinding and low-temperature aging promoted a statistical increase in the fatigue limit (Ctrl<Grinding; Ctrl<Ctrl Ltd; Grinding<Grinding Ltd). An important increase was observed in m-phase content after both stimuli (grinding and LTD), although with different intensities. Additionally, fatigue test did not promote increase of m-phase content. Thus, tested grinding and low temperature aging did not damage the fatigue limit values significantly for both materials evaluated, even though those conditions promoted increase in m-phase.